PEDAGOGICAL CONDITIONS NECESSARY TO IMPROVE THE QUALITY OF THE EDUCATIONAL PROCESS IN PHYSICAL EDUCATION - Rakhimov Abdumalik Abdusattarovich (Proximus Journal Publishing, 2025)
The article presents the authors' research materials on improving the quality of the educational process in the field of physical culture. The authors note that in order to increase the effectiveness of the educational process, it is necessary to create the following conditions: to take into account the interests of students in the organization of classes; for students with a low level of motor activity, it is recommended to include emotional physical exercises in classes (sports and outdoor games, relay races, pair exercises, exercises with subjects, etc.); to develop criteria for assessing academic performance in physical education; in order to widely attract students to regular physical education and sports, the university's sports club needs to conduct mass health, physical education and sports events more often
Keywords: Physical education; sports events; mass health; effectiveness